Wahdatul Ulum Perspektif Ibnu Rusyd: Hakikat Agama dan Filsafat untuk Studi Islam Masa Depan - Nilawati Tajuddin; Muhamad Agus Mushodiq (Bulletin of Indonesian Islamic Studies, 2024)
This paper investigates the concept of wahdatul ulum from the perspective of Ibn Rushd. The researcher utilized qualitative research with a descriptive-historical analysis method. The primary data source for this study is Ibn Rushd's magnum opus, "Faslu Maqal fi Ma Bayna Hikmah wa asy-Syariah min al-Ittisal." The findings suggest that, according to Ibn Rushd, religion and philosophy—being the foundation of science—are fundamentally harmonious. Consequently, the relationship between the two is both absolute and inevitable. It is inconceivable for contradictions to exist between religion and philosophy, as both stem from the same essence: Allah. When apparent contradictions arise, a hermeneutic interpretation is essential to uncover their underlying rationality. In his examination of God’s provisions, Ibn Rushd applies the principle of cause and effect, firmly rooted in rational thought. He places significant emphasis on the importance of logic within religion to prevent individuals from succumbing to the pitfalls of theodicy, apologetics, and dogmatism. Ibn Rushd distinguishes knowledge not by categorizing it as religious or scientific, but by interpreting it as the knowledge of Allah and the knowledge that can be comprehended by humans.